1983
DOI: 10.1007/bf01311200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the major structural proteins of purified bovine viral diarrhea virus

Abstract: Bovine viral diarrhea virus (BVDV) was concentrated and purified by a combination of ultrafiltration, hydroextraction using polyethylene glycol and affinity chromatography. A lectin from Crotalaria juncea that has an affinity for galactose was used in the affinity chromatography. Virions of BVDV with classic envelopes were observed by electron microscopy. Four major proteins with estimated molecular weights of 75,000, 66,000, 54,000, and 26,000 were identified in sodium dodecyl sulfate--polyacrylamide gel elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Virions are 40 to 60 nm in diameter, with a sedimentation coefficient S20w = 140 and a buoyant density of 1.12 to 1.13 in sucrose gradients (see Table 1). 30,64,66,72 The core is composed of a single RNA molecule covered by the nucleocapsid protein p 14/ C. Conclusive determination of the composition of virion envelopes remains elusive. Three glycoproteins seem to be associated with the virion envelope at different stages of maturation: gp48/EO, gp25/El, and gp53/E2.…”
Section: Structure Of the Virion: The Rna Delivery Apparatusmentioning
confidence: 99%
“…Virions are 40 to 60 nm in diameter, with a sedimentation coefficient S20w = 140 and a buoyant density of 1.12 to 1.13 in sucrose gradients (see Table 1). 30,64,66,72 The core is composed of a single RNA molecule covered by the nucleocapsid protein p 14/ C. Conclusive determination of the composition of virion envelopes remains elusive. Three glycoproteins seem to be associated with the virion envelope at different stages of maturation: gp48/EO, gp25/El, and gp53/E2.…”
Section: Structure Of the Virion: The Rna Delivery Apparatusmentioning
confidence: 99%
“…BVDV purified by Coria et al (1983) revealed four major proteins upon Coomassie Brilliant Blue staining of gel-resolved material; two were found to be glycosylated (Table 1, fourth column). Purchio et al (1984a) found three major and two less abundant BVDV-specific proteins ( II Matthaeus (1979).…”
Section: The Proteins Of Pestivirusesmentioning
confidence: 99%
“…Purchio et al (1984a) found three major and two less abundant BVDV-specific proteins ( II Matthaeus (1979). ¶ Coria et aL (1983). ** Purchio et al (1984a).…”
Section: The Proteins Of Pestivirusesmentioning
confidence: 99%
“…As more information becomes available on the replication strategies of some of these viruses, their taxonomic status will be defined more precisely. Molecular studies on the replication of BVD virus have been few, with most studies centred on the structural proteins of the virus or on the antigens released into culture fluids (Purchio et al, 1984;Coria et al, 1983;Matthaeus, 1979;Pritchett & Zee, 1975). We reported previously on the detection of 12 viral polypeptides induced by BVD virus in infected cells (Donis & Dubovi, 1987).…”
Section: Introductionmentioning
confidence: 99%